Analisis Implementasi Koreksi Fiskal Atas Laporan Keuangan Komersial PT ABC - Nabila; Tannar, Oryza (Jurnal Riset Rumpun Ilmu Ekonomi, 2026)
This research uses a qualitative approach by analyzing the fiscal financial statements of PT ABC. The objectives of the research also include identifying the factors that cause discrepancies between the commercial financial statements prepared by taxpayers and the fiscal financial statements that comply with tax regulations. These discrepancies occur due to differences in accounting principles and techniques, including the way revenue and expenses are recognized and managed. To distinguish commercial income statements from fiscal income statements, a calculation basis is used that refers to SAK and applicable tax regulations.